The publification in parliamentary investigations - Villavicencio Rivera, Mónica (2019)
The article defends the necessity to guarantee the publification of the investigative labour carried out in Parliament. This is related to the right of access to public information, enshrined mainly in subsection 5) of Article 2 of the Peruvian Constitution, to the extent that a culture of transparency contributes to build confidence in public management, especially when is concerned with the Parliament, which brings together the representatives elected by the people. Finally, some restrictions on such access and relevant jurisprudence at the constitutional and inter-American level are analyzed.